Contribution of dissolved organic carbon from a tropical river system to the Arabian Sea, southwestern India - Nisha, Baby Krishnan; Balakrishna, Keshava; Udayashankar, Harikripa Narayana; Arun, Kumar; Manjunatha, Busnur Rachotappa (Journal of Asian Earth Sciences: X, 2022)
•Baseline study reporting DOC fluxes from a tropical river in southwestern India.•Post-monsoon season showed higher DOC fluxes compared to the rest of the seasons.•Dense forests of Western Ghats significant contributor of riverine organic carbon.•Payaswini-Chandragiri riverine system contributes 0.4% of DOC flux to the Arabian sea. The Payaswini-Chandragiri river system comprises two small tropical rivers originating in the Western Ghats (Patti Ghats reserve forest) of Peninsular India and contributes to an annual discharge of 4.40 km3 of water into the Arabian sea. This work mainly focuses on the fluxes of total dissolved organic carbon (DOC) from these rivers into the Arabian Sea. Quantifying the amount of terrestrial carbon fluxes into the ocean is important in better understanding long-term climate change because a significant portion of atmospheric carbon dioxide is getting locked up in the ocean sediments. However, DOC fluxes from the tropical southwest flowing rivers of India are sparse, especially in the backdrop of increased human activities since the onset of the Anthropocene. This study is an attempt to fill this gap. The DOC fluxes were measured between April 2016 and Dec 2017 on a seasonal basis. The flux of DOC in the post-monsoon season was 1.3 and 1.2 times higher than the monsoon and the pre-monsoon seasons, respectively. This riverine system contributes ∼0.4% of the total DOC flux received by the Arabian sea.